AN ANALYSIS OF VIEWERS’ RECEPTION ON THE VIDEO MESSAGE “ SAYA MUALAF BILA” ON DEDDY CORBUZIER YOUTUBE CHANNEL - Diana Wahyuni; Yanto Yanto; Sri Narti (SENGKUNI Journal (Social Science and Humanities Studies), 2020)
Youtube is one part of social networking that can create a very close interaction and communication relationship between its users. Inside the YouTube social media account, the account is created by people who basically want to be a part of YouTube content creators. Many people out there who like to play Youtube but do not have the channel account. YouTube channel accounts are made with a variety of content, there are accounts that specialize in making videos of one's daily life, specialist accounts for opinion videos related to issues that are currently hot, specialist accounts for motivational videos, specialist accounts for culinary videos, specialist accounts for videos prank videos and more. What will be the focus of the researcher in this study is the video titled "Saya Mualaf Bila" with views of 3.2 million to this day, views mean that is the frequency of a video is seen. This research method uses purposive sampling supported by Stuart Hall's reception theory. The video is 15 minutes 21 seconds length, in the video Deddy Corbuzer is talking to a religious leader known as Gus Miftah. Deddy Corbuzer talks about religious issues that are rife in Indonesia, causing divisions. The results of this study are the analysis of audience or viewers’ reception of the video message "Saya Mualaf Bila" on Deddy Courbuzier’s YouTube Channel account and the most dominant reception is the interpretation of opposition.